Report to the council on the impediments to express contracts as to the occupation of land in Ireland - McDonnell, Randal W. (Statistical and Social Inquiry Society of Ireland, 1866)
The following Report has been prepared by direction of the Council, in consequence of an application from Jonathan Pim, Esq., M.P., Vice-President, to institute an inquiry into the following subject:? A Report as to the legal and other impediments which still interfere with the proper carrying out of the system of commercial contracts with respect to the occupation of land in Ireland. For such inquiry reference to be had to former Reports of Mr. Robert Longfield, to the Social Inquiry Society, and others. At a meeting of the Council on 12th December, 1865, Mr. Pim being present and concurring, it was resolved "That the intended Report should be, as to the impediments which still interfere with entering into and carrying out of the system of express contracts in respect to the occupation of land in Ireland." The Report having been received, the Council have directed it to be communicated to the members by being inserted in the Journal.
February, 1866
Keywords: Commercial contracts; Land ownership; 314.15